Functional Status and Survival in Older Nursing Home Residents With Advanced Non–Small-Cell Lung Cancer: A SEER-Medicare Analysis. Issue 6 (7th June 2022) - Liu, Michael A.; Keeney, Tamra; Papaila, Alexa; Ogarek, Jessica; Khurshid, Humera; Wulff-Burchfield, Elizabeth; Olszewski, Adam; Bélanger, Emmanuelle; Panagiotou, Orestis A.
Abstract : PURPOSE: Many older patients with advanced lung cancer have functional limitations and require skilled nursing home care. Function, assessed using activities of daily living (ADL) scores, may help prognostication. We investigated the relationship between ADL impairment and overall survival among older patients with advanced non–small-cell lung cancer (NSCLC) receiving care in nursing homes. METHODS: Using the SEER-Medicare database linked with Minimum Data Set assessments, we identified patients age 65 years and older with NSCLC who received care in nursing homes from 2011 to 2015. We used Cox regression and Kaplan-Meier survival curves to examine the relationship between ADL scores and overall survival among all patients; among patients who received systemic cancer chemotherapy or immunotherapy within 3 months of NSCLC diagnosis; and among patients who did not receive any treatment. RESULTS: We included 3, 174 patients (mean [standard deviation] age, 77 [7.4] years [range, 65-102 years]; 1, 664 [52.4%] of female sex; 394 [12.4%] of non-Hispanic Black race/ethnicity), 415 (13.1%) of whom received systemic therapy, most commonly with carboplatin-based regimens (n = 357 [86%] patients). The median overall survival was 3.1 months for patients with ADL score < 14, 2.8 months for patients with ADL score between 14 and 17, 2.3 months for patients with ADL score between 18-19, and 1.8 months for patients with ADL score 20+ (log-rank P < .001). The ADL score was associated with increased risk of death (hazard ratio [HR], 1.20; 95% CI, 1.16 to 1.25 per standard deviation). One standard deviation increase in the ADL score was associated with lower overall survival rate among treated (HR, 1.14; 95% CI, 1.02 to 1.27) and untreated (HR, 1.20; 95% CI, 1.15 to 1.26) patients. CONCLUSION: ADL assessment stratified mortality outcomes among older nursing home adults with NSCLC, and may be a useful clinical consideration in this population.